ANALYZING FACTORS THAT DRIVE PSYCHOLOGICAL PRICING AT PT. MATAHARI DEPARTMENT STORE MEGA MALL MANADO - Lumowa, Pingkan W.R.; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: One way to attract customers is with pricing strategy. Psychological prices have been carried out by marketers, especially retailers. Purpose of this study is to analyze the factors that drive psychological prices at PT. Matahari Department Store Mega Mall Manado. At the beginning of the study there were twenty factors determined as materials for research. This research used quantitative methodology with 100 samples for research. In the results there is one factor that is eliminated because the extraction value is less than 0.5. Nineteen other factors that have been tested are divided into three new factors. These three new factors formed, namely: 1) Consumer Behavior and Consumer Perception, consisting of twelve initial factors. 2) Sales promotion, consisting of three initial factors and, 3) Environment, consisting of four initial factors. In the tests nineteen remaining factors showed a positive correlation. Researcher recommend company to maintain pricing strategy that is applied now but company must keep abreast the developments, rather in the world of fashion as well as marketing strategies that are suitable to be applied. Companies also should continue to innovate in terms of meet the needs and desires of customers. For example company can provide facilities such as waiting room.Keywords: psychological pricing, marketing, pricing strategy, consumer behavior, consumer perception, sales promotion, environment.